Missions, states, and European expansion in Africa - edited by Chima J. Korieh (New York Routledge, 2007)
Missions, States, and European Expansion in Africa aims to explore the ways Christianity and colonialism acted as hegemonic or counter hegemonic forces in the making of African societies. As Western interventionist forces, Christianity and colonialism were crucial in establishing and maintaining political, cultural, and economic domination. Indeed, both elements of Africa?s encounter with the West played pivotal roles in shaping African societies during the nineteenth and twentieth centuries. This volume uses a wide range of perspectives to address the intersection between missions, evangelism, and colonial expansion across Africa. The contributors address several issues, including missionary collaboration with the colonizing effort of European powers; disagreements between missionaries and colonizing agents; the ways in which missionaries and colonial officials used language, imagery, and European epistemology to legitimize relations of inequality with Africans; and the ways in which both groups collaborated to transform African societies.
Includes bibliographical references (p. 279-287) and index.
Keywords: Missions--Africa--History--19th century--Congresses.